Complete Advanced: Workbook with Answers - Matthews L.; Thomas Barbara (Cambridge Cambridge University Press, 2014)
Complete Advanced provides thorough preparation for the revised 2015 Cambridge English: Advanced (CAE) exam. This Workbook with answers consolidates and extends the language and exam skills covered in the Complete Advanced Students Book Second edition. The Audio CD provides all the audio material for the Workbook listening activities. The Workbook audio is also available online as Mp3 files. A Workbook without answers is also available, separately.
Keywords: 811.111